Unleashing animal spirits: Self-control and overpricing in experimental asset markets - Martin Kocher; Konstantin E. Lucks; David Schindler (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
One possible determinant of overpricing on asset markets is a lack of self-control abilities of traders. Self-control is the individual capacity to override or inhibit undesired behavioral tendencies such as impulses and to refrain from acting on them. We implement the first experiment that is able to address a potential causal relationship between self-control abilities and systematic overpricing on financial markets by introducing an exogenous variation of self-control abilities. Our experimental conditions seek to detect some of the channels through which individual self-control problems could transmit into irrational exuberance on the aggregate level. We observe a strong effect of inhibited self-control abilities on market overpricing. Our findings are furthermore robust to reducing self-control abilities only for a moderate share of traders in a market. Low self-control traders engage in more speculative behavior early on, but because others imitate their trading patterns, they do not end up earning less and are not driven out of the market.
urn:nbn:de:bvb:19-epub-27572-2
Keywords: G02; G11; G12; D53; D84; 330; behavioral finance; trader behavior; self control; experimental asset markets; overpricing